Synthesis and Antibacterial Evaluation of Tetrahydropyrimidine-5-carboxamide - Edayadulla, N.; Anand, S.; Shankar, T. (Asian Journal of Chemistry, 2017)
A series of new dihydropyrimidine-2H-ones/thiones were synthesized and evaluated in vitro for their antibacterial activity. Characterization of newly synthesized dihydropyrimidones was done by physical and spectral data. All the synthesized compounds were evaluated for their antibacterial activity. Amongst all, compounds 3e and 4e registered high activity against the bacterial strain when compared to standard drug.